Effect of Bee Resin on Blood Profiles of Infected Carassius auratus by Aeromonas hydrophila - Sri Nuryati; Y. Kuswardani; Y. Hadiroseyani (Jurnal Akuakultur Indonesia)
Bee resin is an organic matter that can be used as immunostimulant to induce cells and tissues regeneration for fast injury recovery. In order to determine the effect of bee resin on blood profile of goldfish, Carassius auratus that had been infected by Aeromonas hydrophila, the numbers of hemoglobin, hetmaocrite, erythrocyte and leukocyte, and leukocyte differentiation were observed.   Fishes were divided into four groups: negative control, positive control, preventive and curative groups. Fishes of negative control were injected intramuscularly by phosphate buffer saline 0.1 ml/fish.  Control positive fishes were injected by 0.1 ml/each of 105 CFU/ml (LD50) A. hydrophila.  Preventive groups were injected by bee resin of 1.5 µl/ml and then injected by 0.1 ml/each of 105 CFU/ml (LD50) A. hydrophila at the eight days after resin injection.  Curative groups were injected first by 0.1 ml/each of 105 CFU/ml (LD50) A. hydrophila before injection with 3 µl/ml resin.  The results of this study showed that erythrocyte number, hemoglobin and hematocrite of goldfish injected by bee resin as prevention were higher compared with positive control groups.  In the curative groups, hematocryte and erythrocyte numbers was comparable with that of positive control groups.  Injection of bee resin intramuscularly for 7 days increased leukocyte number and netrophyle percentage, while other parameters in other treatments were not increased.